1999
DOI: 10.2165/00007256-199927020-00002
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Metabolism and ??-Blocker Therapy

Abstract: The rationale for the concurrent prescription of beta-blockers and programmes of exercise is that both medication and physical activity can improve the quality of life of patients with cardiovascular disease. Difficulties arise when drugs reduce either the physical ability or the motivation to exercise. This article focuses on the physiological limitations to prolonged aerobic exercise in patients receiving beta-blockers. Possible limiting factors to exercise while taking beta-blockers include reduction in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 112 publications
1
13
0
2
Order By: Relevance
“…Blood lactate concentrations were lower in the BETA group at fatigue, which is supported by some investigators (Astrom 1968;Juhlin-Dannfelt and Astrom 1979). However, other studies show conflicting results (Head 1999). In our study, BETA subjects fatigued at lower power outputs, which will inevitably cause a decrease in absolute lactate values.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Blood lactate concentrations were lower in the BETA group at fatigue, which is supported by some investigators (Astrom 1968;Juhlin-Dannfelt and Astrom 1979). However, other studies show conflicting results (Head 1999). In our study, BETA subjects fatigued at lower power outputs, which will inevitably cause a decrease in absolute lactate values.…”
Section: Discussionsupporting
confidence: 77%
“…It is also well documented that an increased perception of effort will reduce exercise performance in healthy individuals who have ingested b-blocker (Joyner et al 1986;Wilmore et al 1985), which is shown in this study by an increase in RPE for BETA. It is has been proposed that this increase in perception of effort results from an inability of healthy individuals to compensate for the decrease in heart rate by increasing stroke volume as it is has been maximised as an adaptation effect of exercise training (Head 1999). These changes in RPE may also be related to neuromuscular recruitment differences as shown in this study.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, mean adipocyte surface was increased in sWAT and eWAT obtained from CAD compared with NCAD patients, suggesting that increased AM synthesis in response to CAD is one of the possible mechanisms that can affect adipocyte size. Because more CAD than NCAD patients were treated with ␤-blockers (9 of 12 vs. 1 of 10, respectively), it can also be suggested that the increased adipocyte surface found in CAD patient was subsequent to an inhibition of catecholamines-induced lipolysis (13). It has been demonstrated that, in patients with chronic heart failure, treatment with ␤-blockers increases total body fat mass (26).…”
Section: Discussionmentioning
confidence: 99%
“…Un argument convaincant de l'implication du SNS dans le contrôle de la DER repose sur la baisse de DER consécutive à l'administration d'un β-antagoniste (propranolol). Les individus ayant la DER ajustée la plus élevée sont ceux qui présentent la diminution la plus importante après administration de propranolol [12,13]. La DER et la DET (sur 24 h) peuvent être influencées par la composition de la ration alimentaire en macronutriments ; notons que des résultats assez disparates ont été rapportés.…”
Section: Système Nerveux Sympathique Et Dépense éNergétiqueunclassified
“…Un blocage pharmacologique efficace du SNS est particulièrement délicat à mettre en oeuvre ; une inhibition partielle de son activité est obtenue avec des antagonistes des récepteurs β-adrénergiques. Un traitement de patients hypertendus par de tels antagonistes est accompagné d'une prise de poids (2 à 5 kg) que l'on peut attribuer à un accroissement de la masse grasse ; cet accroissement de masse grasse est très variable selon les patients et n'exclut pas la participation d'autres voies régulatrices encore mal identifiées [13]. Le niveau d'activation du SNS affectera également la perte de poids de patients obèses soumis à un régime hypocalorique.…”
Section: Système Nerveux Sympathique Prise De Poids Obésité Et Pertunclassified